Chasing the European Dream: Unaccompanied African Youths' Educational Experience in a Canary Islands' Reception Centre and Beyond - Valérie Auger-Voyer; Martha Montero-Sieburth; Lidia Cabrera Perez (Arizona State University, 2014)
In the last two decades, Spain's Canary Islands have received thousands of undocumented migrants arriving by boat from the coasts of North and West Africa. The sharp increase of unaccompanied minors has presented a particular challenge, as these minors fall under the State's protection system and are entitled to an education and other rights, once in Spain. What economic and socio-cultural factors push these youth to seek a better life whilst endangering their own? What educational opportunities are available to them in Spain and how can these propel them into secure living situations? What can be said about their integration prospects? This ethnographic study, based on field research carried out in a reception centre for unaccompanied minors in Tenerife, focuses on the youth's migration trajectories, and on the extent to which the education and support they receive in Spain relates to their socio-economic integration into European society and beyond. The findings reveal that although the centre provides the youth with a window of opportunity to be in Spain and gain an education, the ambiguousness of their legal situation brought about by immigration policies once they have left the centre, is not conducive to their leading a stable and productive life in the current context.